Intentions to Apply as Internship Students on Digital Start-Up Companies in Jakarta - Liza Agustina Maureen Nelloh (Jurnal Ekonomi dan Bisnis, 2017)
Human capital plays an important role in explaining organizational performance and survival, not only for well-established firms but also for digital startup companies. However no previous human resource literature, especially on employers’ brand, investigates the internship program in the startup digital firms. Our pre-test shows that students are less attracted to apply to startup digital companies. Consequently, this study aims to test students’ intention to be on an internship in startup digital companies with its several antecedents (organizational attractiveness, job meaning, organizational attributes, and institutional image). My purposive sampling generates 101 business and management students in Jakarta as my sample. I run Partial Least Square (PLS) to test my hypothesis. The results indicate that organizational attributes do not affect intention to be on an internship and other hypothesis tests exhibit positive results. Further, the findings also show that organizational attributes do not exhibit mediating effect. Overall, the results suggest that digital startup companies cooperate and collaborate with universities, especially business and management departments in research and student projects in order to attract the best students to be on internship on these companies that eventually will improve their performance.AbstrakSumber Daya Manusia memegang peran penting dalam ketahanan dan peningkatan kinerja perusahaan baik berskala besar ataupun berskala startup digital. Akan tetapi, penelitian sebelumnya mengenai sumber daya manusia khususnya merek perekrut yang menguji secara khusus pada program magang yang banyak dilakukan oleh jurusan bisnis dan manajemen atau sejenisnya masih jarang dilakukan. Kemudian, hasil prates menunjukkan rendahnya ketertarikan dan keinginan mahasiswa untuk melamar di perusahaan startup digital. Oleh karena itu, penelitian ini bertujuan untuk menguji intensi melamar calon mahasiswa magang di perusahaan startup digital bersama beberapa antesendennya (ketertarikan organisasi, arti pekerjaan, atribut organisasi, dan citra institusi). Survey purposive sample dilakukan terhadap 101 mahasiswa jurusan bisnis dan manajemen di Jakarta. Partial Least Square (PLS) digunakan dalam penelitian ini untuk menguji hipotesis. Hasil penelitian ini mengindikasikan bahwa atribut organisasi tidak signifikan pengaruhnya terhadap intensi melamar, bersamaan dengan hasil posifitif pada semua uji hipotesis, dan juga membuktikan tidak adanya mediasi variabel atribut organisasi. Hasil penelitian ini menyarankan perusahaan startup digital untuk membina kerjasama dan kolaborasi yang kuat dengan pihak universitas khususnya jurusan bisnis dan manajemen dalam bidang riset dan proyek mahasiswa untuk menarik calon mahasiswa magang yang berkualitas sehingga dapat mencapai kinerja organisasi yang optimal.